2000
DOI: 10.1073/pnas.030420797
|View full text |Cite
|
Sign up to set email alerts
|

Induction of a bystander mutagenic effect of alpha particles in mammalian cells

Abstract: Ever since the discovery of X-rays was made by Rö ntgen more than a hundred years ago, it has always been accepted that the deleterious effects of ionizing radiation such as mutation and carcinogenesis are attributable mainly to direct damage to DNA. Although evidence based on microdosimetric estimation in support of a bystander effect appears to be consistent, direct proof of such extranuclear͞extracellular effects are limited. Using a precision charged particle microbeam, we show here that irradiation of 20%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
281
1
1

Year Published

2001
2001
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 432 publications
(299 citation statements)
references
References 34 publications
15
281
1
1
Order By: Relevance
“…This, however may still be significant, particularly in terms of risk when one considers low doses of relevance to environmental exposures to ionizing radiation, and it may be of relevance to the development of treatments using targeted radionuclides, where not all cells are successfully targeted but may need to rely on a bystander response . Also, it is likely that many cells that survive may be altered, for example, being subject to mutational changes (Nagaswa and Little, 1999;Zhou et al, 2000). In these studies a similar effect is observed in terms of a 3-5 fold increase in the expected levels of mutations, which may also depend on the numbers of cells targeted.…”
Section: Figurementioning
confidence: 56%
“…This, however may still be significant, particularly in terms of risk when one considers low doses of relevance to environmental exposures to ionizing radiation, and it may be of relevance to the development of treatments using targeted radionuclides, where not all cells are successfully targeted but may need to rely on a bystander response . Also, it is likely that many cells that survive may be altered, for example, being subject to mutational changes (Nagaswa and Little, 1999;Zhou et al, 2000). In these studies a similar effect is observed in terms of a 3-5 fold increase in the expected levels of mutations, which may also depend on the numbers of cells targeted.…”
Section: Figurementioning
confidence: 56%
“…Most interestingly, several cytokines can be induced by ROS and NO/NOS (Ayache et al, 2002;Hsu and Wen, 2002;Kosmidou et al, 2002;Hwang et al, 2004;Ryan et al, 2004) providing a possible link between different factors potentially involved in bystander signalling. End points used for the study of bystander effects in vitro have included micronuclei formation (Azzam et al, 2002;Kashino et al, 2004;Shao et al, 2004), gene mutations and genomic instability (Zhou et al, 2000), gene expression changes (Azzam et al, 2002;Yang et al, 2005), transformation (Sawant et al, 2001), proliferation (Gerashchenko and Howell, 2003), cell survival, apoptosis (Belyakov et al, 2002;Lyng et al, 2002), cell cycle arrest (Azzam et al, 2000) and most recently the induction of gH2AX foci in bystander cells (Hu et al, 2005;Sokolov et al, 2005;Yang et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The radiation-induced bystander effect is a phenomenon whereby cellular damage (sister chromatid exchanges (Nagasawa and Little, 1992;Lehnert and Goodwin, 1997), chromosome aberrations (Little et al, 1997;Lorimore et al, 1998), apoptosis (Mothersill and Seymour, 1997;Mothersill et al, 2000), micronucleation (Prise et al, 1998;Belyakov et al, 2001), transformation (Sigg et al, 1997), mutations (Zhou et al, 2000) and changes of gene expression (Hickman et al, 1994;Azzam et al, 1998)) are expressed in unirradiated neighbouring cells close to an irradiated cell or cells. The mechanisms underpinning the bystander effect are not yet known.…”
mentioning
confidence: 99%